Sejarah Dakwah Di Merauke Provinsi Papua - Rubba, Sulhawy (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2015)
Papua is the largest province in Indonesia. Indigenous people embrace animism and dynamism. Located in the central part of the island of Papua, the easternmost part of western Papua (formerly Irian Jaya). In the eastern part is the State of Papua New Guinea. Previously, the province is still join the western part of Papua, but since 2003 is divided into two provinces, the eastern part, kept the name Papua, while the western part of the name of West Papua. Jayapura as a capital city of Papua and West Papua provincial capital called Manokwari. Merauke as one of the 29 districts / cities in the governance system within the Papua Province has an own story about Islamic propagation. The existence of the Islamic community in Merauke originated from the collection of the nomads. Hailing from various parts of the archipelago of the descendants of the Muslim family. They come to Merauke in Papua to perform duties of the state, seeking employment, change or improve the lot of families on government facilities, and some are coming specifically as a preacher and religionist for the propagation of Islam